1929
DOI: 10.1084/jem.50.6.809
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Study of the Precipitin Reaction Between Type Iii Pneumococcus Polysaccharide and Purified Homologous Antibody

Abstract: Of all the reactions of immunity the precipitin test is perhaps the most dramatic and striking. While other immune reactions are more delicate, the precipitin test is among the most specific and least subject to errors and technical difficulties. Attempts at its quantitative interpretation and explanation (1, 2) have been hampered either by the difficulty of finding suitable analytical methodsf or by the failure to separate the reacting substances from closely related, non-specific materials with which they ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

1929
1929
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(60 citation statements)
references
References 5 publications
2
57
0
1
Order By: Relevance
“…12) result in a spatial configuration which is altered when these charges are reduced by high salt concentrations, with a consequent diminution in specificity, or reactivity with corresponding spatially orientated groupings in the antibody molecule. At any rate there is much reason to ascribe an ionic mechanism to this effect, as was originally done in the case of the S IH-antibody reaction itself (10). Salt effects similar to the above have also been noted by Hammarsten and collaborators (13), in the reaction between proteins and nucleic acids.…”
Section: Effect Of Varying Cations and Anions On Reaction Between S Imentioning
confidence: 59%
“…12) result in a spatial configuration which is altered when these charges are reduced by high salt concentrations, with a consequent diminution in specificity, or reactivity with corresponding spatially orientated groupings in the antibody molecule. At any rate there is much reason to ascribe an ionic mechanism to this effect, as was originally done in the case of the S IH-antibody reaction itself (10). Salt effects similar to the above have also been noted by Hammarsten and collaborators (13), in the reaction between proteins and nucleic acids.…”
Section: Effect Of Varying Cations and Anions On Reaction Between S Imentioning
confidence: 59%
“…In this case acid in excess is adsorbable by the resulting compound, and is not traceable in the supernatant fluid in equivalent amount. Heidelberger and Kendall (1929), working with a non-protein antigen from pneumococcus and homologous antisera, have suggested that, in this case, the reaction between antigen and antibody is following a modification of the laws of mass action. They state that more than one type of complex is formed: one part of antibody being capable of reacting with one part of antigen to yield one type of complex, whilst one part of antibody may react with two parts of antigen to form a second type of complex, and so on.…”
Section: Serum Precipitation Reactionmentioning
confidence: 99%
“…This antibody solution is almost entirely free of serum protein other than serum globulin, 90 per cent being removed in its preparation (9). This finding is further evidence, although indirect, in favor of the importance, in the production of the inhibition zone, of modified agglutinin (antibody globulin).…”
Section: Cmentioning
confidence: 57%
“…In support of such a suggested explanation we have observed one serum (pneumococcus, Type I, horse) in which an inhibition zone appeared when incubation was at 56 ° but not at 37 ° . It is of interest in this connection that Heidelberger and Kendall (9) in studying the precipitin reaction have observed flocculation at icebox temperatures in mixtures which showed no precipitation at room temperature. Whenever natural inhibition zone serum is available further investigation will be carried forward.…”
Section: Discussionmentioning
confidence: 99%